Literature Review: Potential of Lamiaceae Terpenoid Compounds as Anti-Inflammatory - Noli, Zozy Aneloi; Sari, Melda Yunita; Khairunnisa, Kania; Yanti, Irda (Jurnal Biologi Tropis, 2026)
Lamiaceae family are rich in natural bioactive compounds, particularly essential oils, with antioxidant, antimicrobial, antifungal, and anti-inflammatory activities, making them a potential source of therapeutic agents for managing inflammation, which is a biological response to tissue damage. This review article aims to provide an overview and analyze the potential of terpenoid compounds from the Lamiaceae family as anti-inflammatory agents. A systematic literature search was conducted using ScienceDirect, PubMed, SciFinder Scholar, EBSCO, and Google Books, covering publications from 2014 to 2025. Using relevant keywords, a total of 100 publications were initially identified. After title and abstract screening, 72 articles were selected for eligibility assessment, of which 20 peer-reviewed research articles reporting in vitro and in vivo anti-inflammatory activities of Lamiaceae terpenoids were analyzed in detail. This study showed that terpene compounds in Lamiaceae essential oils have significant potential to inhibit the production of inflammatory mediators, including cytokines (IL-6, IL-8, IL-1β, IL-2, IL-4, IL-17A, and TNF-α), and nitric oxide (NO). These findings strongly support the Lamiaceae family as a promising source of natural anti-inflammatory agents, warranting further investigation through mechanistic studies, in vivo validation, toxicity assessment, and formulation development to advance their potential therapeutic application.